Adherence to Antihypertensive Medications in Iranian Patients - Azin Behnood-Rod; Omid Rabbanifar; Pirouz Pourzargar; Alireza Rai; Zahra Saadat; Habibollah Saadat; Yashar Moharamzad; Donald E. Morisky (International Journal of Hypertension)
Introduction. Appropriate adherence to medication is still a challenging issue for hypertensive patients. We determined adherence to antihypertensive(s) and its associated factors among 280 Iranian patients. Methods. They were recruited consecutively from private and university health centers and pharmacies in four cities. The validated Persian version of the 8-item Morisky Medication Adherence Scale (MMAS-8) was administered to measure adherence. Results. Mean (±SD) overall MMAS-8 score was 5.75 (±1.88). About half of the sample (139 cases, 49.6%) showed low adherence (MMAS-8 score < 6). There was a negative linear association between the MMAS-8 score and systolic BP (r=-0.231, P<0.001) as well as diastolic BP (r=-0.280, P<0.001). In linear regression model, overweight/obesity (B=-0.52, P=0.02), previous history of admission to emergency services due to hypertensive crisis (B=-0.79, P=0.001), and getting medication directly from drugstore without refill prescription in hand (B=-0.51, P=0.04) were factors recognized to have statistically significant association with the MMAS-8 score. Conclusion. Antihypertensive adherence was unsatisfactory. We suggest that health care providers pay special attention and make use of the aforementioned findings in their routine visits of hypertensive patients to recognize those who are vulnerable to poor adherence.